2022
DOI: 10.1093/europace/euac053.280
|View full text |Cite
|
Sign up to set email alerts
|

Detection of atrial fibrillation in patients with cryptogenic stroke: The Nordic Atrial Fibrillation and Stroke (NOR-FIB) study - topline results

Abstract: Funding Acknowledgements Type of funding sources: Other. Main funding source(s): NOR-FIB is an investigator driven academic study. 100 of 259 devices are supported by Medtronic. BRT and ATL are recipients of a PhD grants from the South-Eastern Norway Regional Health Authority. The study is supported by the research infrastructure of the European Cerebrovascular Research Infrastructure (ECRI). Background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Another novel finding in our study is the high incidence of recurrent strokes occurring in patients without ILR detected arrhythmia ( n = 27, 87.1% of total recurrent strokes). Previous European studies have reported variable rates of recurrent stroke following CS in the absence of ILR detected AF, ranging from around 50%–80% 14,15 . The higher proportion of recurrent strokes in our study may partly be accounted for by the high proportion of African American patients.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Another novel finding in our study is the high incidence of recurrent strokes occurring in patients without ILR detected arrhythmia ( n = 27, 87.1% of total recurrent strokes). Previous European studies have reported variable rates of recurrent stroke following CS in the absence of ILR detected AF, ranging from around 50%–80% 14,15 . The higher proportion of recurrent strokes in our study may partly be accounted for by the high proportion of African American patients.…”
Section: Discussionmentioning
confidence: 49%
“…Previous European studies have reported variable rates of recurrent stroke following CS in the absence of ILR detected AF, ranging from around 50%-80%. 14,15 The higher proportion of recurrent strokes in our study may partly be accounted for by the high proportion of African American patients.…”
Section: Characteristicmentioning
confidence: 69%
“…Another novel nding in our study is the high incidence of recurrent strokes occurring in patients without ILR detected arrhythmia (n = 27, 87.1% of total recurrent strokes). Previous European studies have reported variable rates of recurrent stroke following CS in the absence of ILR detected AF, ranging from around 50-80% [14,15]. The higher proportion of recurrent strokes occurring in the absence of detected AF in the current study may also partly be accounted for by the high proportion of African American patients.…”
Section: Discussionmentioning
confidence: 52%
“…To the best of our knowledge, there is only 1 available study in the literature evaluating different risk scores for AF prediction in a Norwegian cohort of patients with CS. 43 This study evaluated 8 clinical risk scores in 259 patients with CS or cryptogenic transient ischemic attack. The results of this study are not directly comparable to our findings, given differences in score selection (C 2 HEST score was not evaluated in the Norwegian study), patient selection (patients with transient ischemic attack were not included in our study), and duration of ICM [≤12 months in the Norwegian study and median duration of 16 months (IQR, 8–25) in our study].…”
Section: Discussionmentioning
confidence: 99%